Chironomid-climate continentality conundrum - Varvara Bakumenko; Anneli Poska; H. John B. Birks; Brian Huser; Siim Veski (PLoS ONE, 2025)
It is predicted that continentality, a climate parameter representative of a region’s annual temperature and precipitation range, will undergo significant changes in the future. The lack of past continentality reconstructions makes it impossible to decipher any long-term patterns of continentality changes. Here, we investigate the extent to which continentality influences modern chironomid assemblages and evaluate their ecological relevance for palaeolimnological data-based reconstructions of past continentality. We selected 53 lakes along a longitudinal gradient covering the East European Plain (Western part of Russia, Estonia, Latvia) and southern Scandinavia (Sweden and Norway). We analysed the dependency of chironomid assemblages on a variety of environmental parameters including two continentality indices (annual temperature range (ATR) and the Kerner Oceanity Index (KOI)), growing degree days at base temperature 5 °C, mean air temperatures of July, April, and October, number of ice-cover days, lake-water pH, loss-of-ignition and water depth using redundancy analysis. Correlations between all variables were tested to check for possible confounding effects. KOI had the highest explanatory power of 18.4% in the dataset and an absence of collinearity (correlation index < 0.7) with all the other tested variables. Further, we estimated weighted average optima to investigate the distribution of the morphotypes along the continentality gradient in the dataset. Glyptotendipes pallens-type, Neozavrelia, Polypedilum sordens-type, and Microchironomus showed a preference for a continental climate, while Paratanytarsus penicillatus-type, Pseudorthocladius, Thienemannimyia, and Limnophyes were found mainly in samples from oceanic areas. Weighted averaging-partial least squares regression was used for a trial test of the data, resulting in a promising KOI-based model performance with R2 = 0.73 and RMSEP = 5.1. Despite the relatively small dataset, our study suggests that chironomid data have the potential for further development as a tool for reconstructing palaeocontinentality.